USING FREE4TALK AS LEARNING MEDIA IN BOOSTING JUNIOR HIGH SCHOOL STUDENTS’ SPEAKING SKILLS - Ali, Rehan Zainal; Zaitun, Zaitun (Universitas Tanjungpura, 2026)
This study investigates the effectiveness of Free4Talk, as learning media, to improve junior high school students’ speaking skills. The research employed quantitative pre-experimental method with one group pre-test and post-test design. There were 34 students of grade 8 participated as research sample. They were registered at Rubath Nurul Musthofa Islamic Boarding School, where this research took place on even semester of 2024/2025 academic year. In data collection, pre-test and post-test of speaking skills were used as the instruments. The data were analyzed statistically using paired-sample t-test. The calculation of the data revealed that t-test value of 19.44 was far higher than the t-table value of 1.692 in the significance level of 5%. This result confirmed that there was a difference on students’ speaking achievement in the pre-test and post-test in which the students performed better in the post-test. The analysis data covered speaking components including pronunciation, fluency, vocabulary, and self-confidence. These findings rejected H0 and accepted Ha. To sum, in this research work, Free4Talk was said to be effective to improve students’ speaking skills.